2002
DOI: 10.1016/s0140-6736(02)08652-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative fondaparinux versus preoperative enoxaparin for prevention of venous thromboembolism in elective hip-replacement surgery: a randomised double-blind comparison

Abstract: Drugs that act through specific inhibition of factor Xa, such as fondaparinux, could be more effective than low molecular weight heparins in prevention of venous thromboembolism in patients undergoing hip-replacement surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
288
1
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(310 citation statements)
references
References 24 publications
15
288
1
6
Order By: Relevance
“…Two venography-based studies have shown that fondaparinux is effective for prevention of VTE in patients undergoing total hip replacement. 46,47 In a European study, fondaparinux given at the dose of 2.5 mg once daily starting 4 to 8 hours after surgery significantly reduced the incidence of DVT from 9% to 4% in comparison with enoxaparin given at a dose of 40 mg once daily starting 12 hours before surgery. The rate of proximal DVT also was significantly reduced by fondaparinux from 2% to 1%.…”
Section: Elective Hip Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…Two venography-based studies have shown that fondaparinux is effective for prevention of VTE in patients undergoing total hip replacement. 46,47 In a European study, fondaparinux given at the dose of 2.5 mg once daily starting 4 to 8 hours after surgery significantly reduced the incidence of DVT from 9% to 4% in comparison with enoxaparin given at a dose of 40 mg once daily starting 12 hours before surgery. The rate of proximal DVT also was significantly reduced by fondaparinux from 2% to 1%.…”
Section: Elective Hip Replacementmentioning
confidence: 99%
“…The rate of proximal DVT also was significantly reduced by fondaparinux from 2% to 1%. 46 In a North American trial, the same fondaparinux regimen was compared with enoxaparin 30 mg twice daily started 12 to 24 hours after surgery. 47 In this study, the rate of overall VTE was reduced from 8% to 6% (PϭNS) in the fondaparinux group.…”
Section: Elective Hip Replacementmentioning
confidence: 99%
“…Platelet count data were reviewed for the 37 SRA-positive patients, with the last available platelet count value obtained a median (interquartile range) of 8 (7,8) days after the first administration of study drug. One of these 37 SRA-positive patients met our criteria for clinical HIT (Fig.…”
Section: Patient With Clinical Hitmentioning
confidence: 99%
“…It has been developed to provide a selective anticoagulant effect and to overcome some side effects of LMWH such as allergic reactions [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%